Development of a new assessment scale for measuring interaction during staff-assisted transfer of residents in dementia special care units - Thunborg, Charlotta (BMC Geriatr, 2015)
BACKGROUND: Mobility problems and cognitive deficits related to transferring or moving persons suffering from dementia are associated with dependency. Physical assistance provided by staff is an important component of residents’ maintenance of mobility in dementia care facilities. Unfortunately, hands-on assistance during transfers is also a source of confusion in persons with dementia, as well as a source of strain in the caregiver. The bidirectional effect of actions in a dementia care dyad involved in transfer is complicated to evaluate. This study aimed to develop an assessment scale for measuring actions related to transferring persons with dementia by dementia care dyads. METHODS: This study was performed in four phases and guided by the framework of the biopsychosocial model and the approach presented by Social Cognitive Theory. These frameworks provided a starting point for understanding reciprocal effects in dyadic interaction. The four phases were 1) a literature review identifying existing assessment scales; 2) analyses of video-recorded transfer of persons with dementia for further generation of items, 3) computing the item content validity index of the 93 proposed items by 15 experts; and 4) expert opinion on the response scale and feasibility testing of the new assessment scale by video observation of the transfer situations. RESULTS: The development process resulted in a 17-item scale with a seven-point response scale. The scale consists of two sections. One section is related to transfer-related actions (e.g., capability of communication, motor skills performance, and cognitive functioning) of the person with dementia. The other section addresses the caregivers’ facilitative actions (e.g., preparedness of transfer aids, interactional skills, and means of communication and interaction). The literature review and video recordings provided ideas for the item pool. Expert opinion decreased the number of items by relevance ratings and qualitative feedback. No further development of items was performed after feasibility testing of the scale. CONCLUSIONS: To enable assessment of transfer-related actions in dementia care dyads, our new scale shows potential for bridging the gap in this area. Results from this study could provide health care professionals working in dementia care facilities with a useful tool for assessing transfer-related actions. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12877-015-0003-6) contains supplementary material, which is available to authorized users.